A methodology exploiting geographical information systems to site a photovoltaic park inside a sustainable community. Issue 2 (7th February 2016) - Tsikalakis, A.; Routsis, D.; Pafilis, A.; Kalaitzakis, K.; Stavrakakis, G.
Abstract : This paper describes a methodology for applying geographical information systems (GIS) tools to site a photovoltaic (PV) park inside a sustainable community, in order, not only to meet all siting restrictions, such as environmental protection, but also to operate a PV park more efficiently reducing the shading effect erection and cabling cost. Additionally, the PV operation impact on the grid is investigated, integrating GIS maps into power systems analysis software, such as the PowerWorld ® Simulator. In other words, this paper also stresses the importance of GIS for the design, installation and monitoring of power systems. A case study considering the Campus of the Technical University of Crete has been performed showing that siting properly a PV installation meeting 20% of the demand can gain significant savings in both peak and regular energy demands, especially on peak summer days.